Study of A Ferroelectric Liquid Crystal Mesogen by Geometrical Optimization and Electro-Optic Characterization - Goswami, D. (Journal of Scientific Research, 2024)
In the present work one biphenyl benzoate cored liquid crystal was characterized using geometrical optimization and electro-optic study. Geometry of the molecule was optimized using Hartree-Fock method with 3-21G basis. The simulated value of molecular length and dipole moment was reported. The Infrared (IR) spectra were also simulated and analyzed. The energy gap between highest occupied molecular orbit (HOMO) and lowest unoccupied molecular orbit (LUMO) was calculated. The phase transition temperatures and phase sequences were identified by observing the topological defects in the optical textures at different temperatures under polarizing microscope. It exhibited ferroelectric smectics C* (SmC*) phase for a wide range of temperature and then directly melted into isotropic phase. The optical tilt angle of the compound was measured in SmC* phase and was fitted with mean field model to explore the nature of phase transition. The applicability of the compound for display applications were judged based on the parameters measured.